1978
DOI: 10.1113/jphysiol.1978.sp012380
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the morphological reaction of platelets to aggregating agents and of its reversal by aggregation inhibitors.

Abstract: SUMMARY1. In rabbit citrated platelet-rich plasma, the changes in shape of the platelets produced by adenosine diphosphate (ADP) or 5-hydroxytryptamine (5-HT) were observed by photometric and volumetric techniques and by measurements of platelet images on electron micrographs either directly or with an image analysing computer. This permitted the indirect manifestations of the shape changes to be correlated with the morphological features responsible for them, i.e. transformation of disks to more spherical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 18 publications
3
39
0
2
Order By: Relevance
“…In contrast to the results obtained with general photometers (O'Brien, 1962), an initial decrease in transmission was observed with the devices specifically designed for platelet aggregometry by Born (Born et al, 1978;Latimer et al, 1977). It was suggested that this optical effect was caused by the morphological change of platelets from discs to spherical cells with pseudopodia (Latimer et al, 1977).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…In contrast to the results obtained with general photometers (O'Brien, 1962), an initial decrease in transmission was observed with the devices specifically designed for platelet aggregometry by Born (Born et al, 1978;Latimer et al, 1977). It was suggested that this optical effect was caused by the morphological change of platelets from discs to spherical cells with pseudopodia (Latimer et al, 1977).…”
mentioning
confidence: 70%
“…The initial decrease in light transmission was first observed with devices specifically designed for platelet aggregometry by Born (Born et al, 1978;Latimer et al, 1977), in which the angle of light collection is small. Based on theoretical calculations, Latimer (1983) predicted that in a Born-type aggregometer microaggregation leads to a decrease in light transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, 5-HT produced its characteristic shape-changing effects on the platelets (Born, Dearnley, Foulks & Sharp, 1978) which was clearly demonstrable (Figure la).…”
Section: Resultsmentioning
confidence: 93%
“…This change can be quantified by measuring the light absorption of the platelet suspension (Born, Dearnley, Foulks & Sharp, 1978). One group of shape change-inducing agents, represented by substances like 5-hydroxytryptamine (5-HT) and adenosine 3', 5'-diphosphate (ADP), probably acts through specific receptors at the plasma membrane, as has been shown by shape change and binding studies with specific agonists and antagonists of 5-HT and ADP receptors (Born, 1970;Drummond, 1976;Adler & Handin, 1979).…”
Section: Introductionmentioning
confidence: 99%